2017
DOI: 10.1142/s021919971650036x
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing-concentration-compactness alternative for the Trudinger–Moser inequality in ℝN

Abstract: and ω N−1 is the surface measure of the (N − 1)-dimensional unit sphere in R N . We obtain a vanishingconcentration-compactness alternative showing that maximizing sequences for d N (a, b) cannot concentrate either when b = N or when b = N and a > 0 is sufficiently small. From this alternative, we deduce the attainability of d N (a, b) for special values of the parameters a and b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Proof of Theorem When β=0 and a2, it was proved in (see also ) that TMa,2,04π>4π. Hence in this case if 4πa2πe, that is a8e, then by combining this with Lemma and Lemma , we get that trueprefixlims01s4πa2s4πSTM0s<TMa,2,04πand trueprefixlims4π1s4πa2s4πSTM0s<TMa,2,04π.This, together with Lemma and the identity , give us that there exists s0,4π such that 1s4πa2s4πSTM0s=T<...>…”
Section: Proof Of Theoremmentioning
confidence: 75%
See 2 more Smart Citations
“…Proof of Theorem When β=0 and a2, it was proved in (see also ) that TMa,2,04π>4π. Hence in this case if 4πa2πe, that is a8e, then by combining this with Lemma and Lemma , we get that trueprefixlims01s4πa2s4πSTM0s<TMa,2,04πand trueprefixlims4π1s4πa2s4πSTM0s<TMa,2,04π.This, together with Lemma and the identity , give us that there exists s0,4π such that 1s4πa2s4πSTM0s=T<...>…”
Section: Proof Of Theoremmentioning
confidence: 75%
“…Thus, in this case, we have trueprefixlimndouble-struckR2e4π1β2||vn21xβdx=0. Case 2 : BRc||vn2dx0 for all R>0. In this case, ()vn is a maximizing (radial) normalized concentrating sequence (see ). Set truerightrleft=et/2,rightwn()tleft=4π1/2vn()r,we can easily check that trueleftR2||vn2dx=14||wnt2etdt;leftR2||vn2dx=||wnt2dt;leftR2exp…”
Section: Proof Of Theoremmentioning
confidence: 94%
See 1 more Smart Citation
“…For proving the existence of a maximizer of C N,α or D N,α (a, b) with α < α N , we need to avoid the lack of the compactness. In this case, concentration phenomena do not occur (see [10,Lemma 4.2]) and vanishing phenomena are issues due to the unboundedness of the domain. Concerning the maximizing problem D N,αN (a, b) with b ≤ N , we may also suffer from the lack of the compactness caused by the concentration.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Moreover, the author in [12] also proved the non-existence of a maximizer when N = 2 and 0 < α ≪ 1. For general a and b, the authors in [10] showed that D N,α (a, b) is attained when N ≥ 2, α = α N , a > N ′ and 0 < b < N .…”
Section: Introduction and Main Resultsmentioning
confidence: 99%